2021
DOI: 10.3390/mi12070777
|View full text |Cite
|
Sign up to set email alerts
|

Space Electroosmotic Thrusters in Ion Partitioning Soft Nanochannels

Abstract: Space electroosmotic thrusters (EOTs) are theoretically investigated in a soft charged nanochannel with a dense polyelectrolyte layer (PEL), which is considered to be more realistic than a low-density PEL. When the PEL is dense, its permittivity is smaller than the one of the electrolyte solution layer, leading to rearrangement of ions in the channel, which is denoted as the ion partitioning effect. It is noted that fluid viscosity becomes high within the PEL owing to the hydration effect. An analytical soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Moreover, the applied axial electric field is set as 5 × 10 8 V/m with a voltage drop between the electrodes of 500 V for a 1 µm length channel, which is for producing the needed force and energy for space propulsion. The value of the voltage drop as high as 500-700 V has been used in molecular dynamic simulations of EOF for water solutions [5,6,20,21,40,41,48]. As the steric factor is zero, the problem becomes independent of the steric effect, which has been performed in previous studies [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the applied axial electric field is set as 5 × 10 8 V/m with a voltage drop between the electrodes of 500 V for a 1 µm length channel, which is for producing the needed force and energy for space propulsion. The value of the voltage drop as high as 500-700 V has been used in molecular dynamic simulations of EOF for water solutions [5,6,20,21,40,41,48]. As the steric factor is zero, the problem becomes independent of the steric effect, which has been performed in previous studies [20].…”
Section: Resultsmentioning
confidence: 99%
“…We had considered the influence of soft nanochannel on the electroosmotic thrusters and found that the thruster could achieve efficiency up to 90% and deliver thrust at about 0-20 µN when the soft material was dense [20,21]. When the PEL is dense, its dielectric permittivity is lower than the bulk aqueous medium, resulting in the rearrangement of ions in the channel, which is denoted as the ion partitioning effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanopores, nanopipettes, and nanochannels have various applications such as in biological sensing, 1,2 biological separation, 3 energy conversion, 4,5 water desalination, 6 etc. Accordingly, the understanding and control of the transport phenomena, especially ionic transport, in such elements have been the subject of many research studies during the past two decades.…”
Section: Introductionmentioning
confidence: 99%
“…Huang and Huang [ 15 ] further combined nano electrokinetic thrusters with two-liquid electro-osmotic flows and analyzed performances of the thrusters under the small wall zeta potential. Zheng and Jian [ 16 , 17 ] investigated the influence of the soft nanochannel on the electro-osmotic thrusters and found that the thruster could achieve an efficiency as high as 90% and deliver a thrust of about 0–20 μN.…”
Section: Introductionmentioning
confidence: 99%